A modified surgical technique for children recurrent popliteal cyst: the repair method of using medial head of gastrocnemius tendon flap - Li, Jun; Xiao, Zhixiang; Chen, Jingyi; He, Shaohua; Xu, Di; Chen, Jianglong; Kang, Yingquan (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the efficacy of gastrocnemius medial head tendon flap repair in the treatment of recurrent popliteal cysts in children.MethodsA retrospective analysis was conducted on the data of 65 cases of recurrent popliteal cysts in children admitted to our department from January 2014 to December 2023. Preoperatively, the popliteal cysts were graded according to the Rauschning and Lindgren grading: Grade 0 in 1 case, Grade I in 10 cases, Grade II in 23 cases, and Grade III in 31 cases. The preoperative Lysholm score of the affected knee joint was (71.79 ± 5.95) points. During the operation, after the removal of the popliteal cyst, the medial head of gastrocnemius tendon flap repair was performed to close the joint capsule hernia orifice. The clinical efficacy was assessed by comparing the Rauschning and Lindgren popliteal cyst grading and the Lysholm score of the affected knee joint preoperatively and at 1, 6, 12, and 24 months postoperatively.ResultsAll 65 cases were followed up. No significant neurological complications occurred postoperatively in any case. At the last follow-up, no limitations in knee joint motion were observed. The surgical duration ranged from 30 to 165 min, with a mean of (74.18 ± 28.16) minutes; intraoperative blood loss ranged from 10 to 30 ml, with a mean of (17.43 ± 5.36) ml; and the postoperative hospital stay ranged from 2 to 6 days, with a mean of (3.03 ± 1.91) days. At 1, 6, 12, and 24 months postoperatively, the Rauschning and Lindgren popliteal cyst grading and the Lysholm score of the affected knee joint showed significant improvement compared with preoperative values, with statistically significant differences (P < 0.05). The grading and scores at 6, 12, and 24 months postoperatively were significantly better than those at 1 month postoperatively, with statistically significant differences (P < 0.05). However, no significant differences were observed in the grading and scores between 6, 12, and 24 months postoperatively (P > 0.05). No recurrence was detected in any case during the regular follow-up examinations.ConclusionThe gastrocnemius medial head tendon flap repair can effectively reinforce the hernial orifice between the popliteal cyst and the knee joint cavity, achieving good therapeutic efficacy in treating recurrent popliteal cysts in children.